2019
DOI: 10.5187/jast.2019.61.4.216
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hot melt extrusion processed nano-iron on growth performance, blood composition, and iron bioavailability in weanling pigs

Abstract: This study was conducted to investigate the effects of hot melt extrusion (HME) nano-iron as an alternative for the common ferrous sulfate on iron (Fe) bioavailability, growth performance, nutrient digestibility, intestinal morphology, and intestinal microbiota of weanling pigs. A total of 200 piglets (Landrace × Yorkshire × Duroc) were randomly allotted to seven treatments on the basis of initial body weight (BW) and sex. Treatments were the INO100 (100 ppm Fe as FeSO 4 ), HME-Fe levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
(40 reference statements)
2
19
0
Order By: Relevance
“…Through the HME process, inorganic Cu (CuSO 4 ) was spread out, mixed with insolvent, and prepared for the present study. As known in the previous study, the HME technique already used in the drug industry via solid dispersion formulation even product as low level in water-soluble drugs [ 12 , 13 ]. Moreover, the soluplus as the main polymer matrix was applied in the HME process to optimize the solubility and bioavailability due to high amphiphilic characteristics [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through the HME process, inorganic Cu (CuSO 4 ) was spread out, mixed with insolvent, and prepared for the present study. As known in the previous study, the HME technique already used in the drug industry via solid dispersion formulation even product as low level in water-soluble drugs [ 12 , 13 ]. Moreover, the soluplus as the main polymer matrix was applied in the HME process to optimize the solubility and bioavailability due to high amphiphilic characteristics [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The opposite of our results was obtained using nano-iron by hot melt extrusion (HME, 100 ppm Fe) as an alternative to ferrous sulphate. In many studies, the feed concentration of iron contained in nano particles ranges from 100 to 350 mg/kg feed [ 49 , 50 ]. It has been shown that the dietary nano-iron supplementation does not significantly improve the growth performance of weanling pigs [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, the feed concentration of iron contained in nano particles ranges from 100 to 350 mg/kg feed [ 49 , 50 ]. It has been shown that the dietary nano-iron supplementation does not significantly improve the growth performance of weanling pigs [ 50 ]. Similarly, in our experiment, the growth of IONPs-supplemented piglets in the first days of life was relatively high but not significantly different from anemic animals, in which significant growth stunting was observed in comparison to FeDex-supplemented piglets.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HME-Cu increased the Cu content of the liver compared to the control, and reduced the Cu content of the feces compared to the IN-Cu-supplemented diets. Our previous studies reported that HME improved the bioavailability and metabolic function of minerals, which in turn decreased the fecal mineral output in weanling pigs and broiler chickens [23,24,25,26,27,28]. Similarly, in chickens, diet supplementation with 20 mg/kg of inorganic and organic Cu increased the Cu content of their liver; and in weanling pigs, diet supplementation with 50 mg/kg of nano-Cu reduced their fecal Cu content compared to diet supplementation with 50 mg/kg of inorganic Cu [41,52].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Previous studies showed that HME-processed trace elements had the reduced particle size to nano by the addition of pharmaceutical excipients in order to increase the solubility and dispersion of trace elements [21,22]. Our previous studies have shown the improved bioavailability and metabolic function of HME-processed trace minerals in weanling pigs and broilers [23,24,25,26,27,28]. To evaluate the extent of the nano-process effect on minerals bioavailability in broiler chickens many studies are required, particularly that there are insufficient reports about these technologies at present.…”
Section: Introductionmentioning
confidence: 99%